Determination of Quality of Life for Patients with Essential Hypertension: A Comparative Study - Aqeel H. Jasim (Iraqi National Journal of Nursing Specialties, 2023)
Objectives:TodeterminethequalityoflifeforpatientswithessentialhypertensioninBaghdadcity. Metliodology: A descriptive study was caried out by using a comparative design. The study was initiated from December 2007 through August 2008. A multi-stage probability sampling (Stratified sampling) was used for selecting the sample settings (public medical clinics in Baghdad city). A pulposive "non-probability" sample of (400) participants; half of them were diagnosed as having essential hypellension and the other half was normoteusive individuals. Data were obtained through stmctured interview for both groups in a similar way, in the same place and by the same questionnaire. A questiormaire was adopted and developed from the World Health Organization Quality of Life Scale (1998) andcon§istsofthreeparts:Sociodemographiccharacteristics,Medicaldata,andthethirdpartthatconsistofsix domainsofqualityoflife.Validityofquestiormairewasdeterminedthrougbpresentingthequestionnaireto(15) :::C£:1:tt£:Ppee:[SodanodfEee’ia#2%£¥:oq8uisrt;°unfafaear¥S]8&t:Foi8?edthroughthepilotsutywhichwascanied Data were analyzed through descriptive data analysis approach (Frequency, Percentage, Arithmetic mean, Standard deviation) and the inferential data analysis approach (Multiple Linear Regressions, K-test Z-test, Mann-Whitney test, Contingency Coefficient, Spearman correlation). Results:Theresultsrevealedthatthemajorityofbothgroupswasof(60-69)yearsoldage,married,donotread and write, and unemployed. Most of those who diagnosed as essential hypertensive patients having disease for (6-10) years, suffering from overweight (41%), non controlling their blood pressure level (71 %), having poor qualityoflifeinphysicaldomain(P<0.001),andpsychologicaldomain(P<0.05). The study concluded that essential hypeltensive patients had more deterioration jn most quality of life domains Recommendations: The study recommended that an education program should be designed and manuals should be distributed to essential hypertensive patients to increase their information about the disease to improve their quality of life.